The mystery of post-cholecystectomy persistent bile leak: a case report - Shakeel, Osama; Haroon, Muhammad; Khan, Muhammad Imran; Ammar, Ahmed Siddique; Atiq, Muhammad; Hanif, Faisal (Journal of the Pakistan Medical Association, 2023)
Laparoscopic cholecystectomy (LC) is commonly performed for benign gallbladder diseases. Biliary leak is the most common complication of bile duct injury following this surgery. We report a case of persistent bile leak following the procedure despite endoscopic and radiological management. A female patient presented to the hepatopancreatobiliary unit of the Bahria International Hospital (Orchard), Lahore, with complaint of persistent bile leakage after laparoscopic cholecystectomy performed elsewhere. She had been investigated in various hospitals but the cause of the persistent bile leak remained a mystery and she was offered surgery. After real time fluoroscopic contrast enhanced imaging, further confirmed by a Computerised Tomography (CT) Scan of the abdomen, it was revealed that the persistent bile leak in the drain was due to iatrogenic injury of the duodenum secondary to percutaneous catheter insertion. The patient was managed non-surgically. ---Continue